Fourth Five-Year Plan Madras State Review of Progress During 1966-67 and Programme for 1967-68 - Planning Commission (Planning Commission, 1966)
The object of the scheme is to establish 230 state seed farms in units of 25 acres each for the production of foundation (primary) seeds. It has been estimated that a total of 230 state seed farms, in units of 25 acres each, will be sufficient for the production of the primary paddy and millet seeds required to produce secondary seeds to cover one-third of the area under these crops in the State every year. By the end of the second plan period, 134 units were established. During the third plan period, another 66 units were established bringing the total to 200 units.
Finance Department, Government of Madras